Characterization of Carbapenem-Resistant Enterobacteriaceae Cultured From Retail Meat Products, Patients, and Porcine Excrement in China - Feng, Jie; Xiang, Qian; Ma, Jiangang; Zhang, Pei; Li, Kun; Wu, Ke; Su, Mengru; Li, Ruichao; Hurley, Daniel; Bai, Li; Wang, Juan; Yang, Zengqi (Frontiers in Microbiology, 2021)
The emergence and dissemination of carbapenem-resistant Enterobacteriaceae (CRE) is a growing concern to animal and public health. However, little is known about the spread of CRE in food, livestock and potential transmission to humans. To identify CRE strains from different origins and sources, 53 isolates were cultured from 760 samples including retail meat products, patients and porcine faeces. Antibiotic susceptibility testing was carried out, followed by phylogenetic typing, whole-genome sequencing, broth mating assays and plasmids analyses. Forty-three Escherichia coli, 9 Klebsiella pneumoniae, and 1 Enterobacter cloacae isolates were identified with each exhibiting multidrug-resistant phenotypes. Genetically, the main STs of E. coli were ST156 (n=7), ST354 (n=7) and ST48 (n=7), and the dominant ST of K. pneumonia is ST11 (n=5). BlaNDM-5 (n=40) of E. coli and blaKPC-2 (n=5) were the key genes that conferred carbapenem resistance phenotypes in these CREs. Additionally, the mcr-1 gene was identified in 17 blaNDM-producing isolates. The blaNDM-5 genes from 8 strains could be transferred to the recipients via conjugation assays. Two mcr-1 genes in the E. coli isolates could be co-transferred along with the blaNDM-5 genes. IncF and IncX3 plasmids have been found to be predominantly associated with blaNDM genes in these strains. Strains isolated in our study from different sources and regions tend to be concordant and overlap. CREs from retail meat products are a reservoir for transition of CREs between animals and humans. These data also provide evidence of the dissemination of CRE strains and carbapenem-resistant genes between animal and human sources.